Soil attributes and coffee yield in an agroforestry system - Jácome, Máximo Gerardo Ochoa; Mantovani, José Ricardo; Silva, Adriano Bortolotti da; Rezende, Tiago Teruel; Landgraf, Paulo Roberto Corrêa (Coffee Science - ISSN 1984-3909, 2020)
Coffee growing in an agroforestry system may provide improvements in soil chemical and physical attributes, increase crop yield and diversify production. However, there are few studies on coffee growing intercropped with high quality wood-producing species such as African mahogany, teak and Australian cedar. The objective of this study was to evaluate, in an agroforestry system, the effect of coffee intercropping with tree species and the density of these species on chemical and physical soil attributes and on coffee yield. The experiment was carried out in Santo Antônio do Amparo, MG, and ‘Catucaí’ coffee was used in a 3.4x0.7m spacing. A randomized block design with split plots was used, with one additional treatment and 4 replications. The treatments consisted, in the plot, of three tree forest species: Australian cedar, teak and African mahogany, used intercropped with coffee; and, in the subplots, two densities of these forest species: 82 plants ha-1 (13.6 m between rows and 9 m between plants) and 41 plants ha-1 (13.6 m between rows and 18 m between plants). The additional treatment consisted of conventional coffee growing under full sun. 64 months after the experiment was set, when the forest species were still under development, soil samples were taken at a depth of 0 to 0.1 m to determine the following chemical attributes: pH in H2O, potential acidity, organic matter content, P-Mehlich, K+, Ca2+, Mg2+, S, B, Cu, Fe, Mn, Zn and base saturation (V%); and physical soil attributes: bulk density, macroporosity, microporosity, total porosity. Soil temperature at 0.05 m depth and coffee yield were also evaluated. Chemical and physical attributes, besides soil temperature, are similarly influenced with the cultivation of Australian cedar, teak and African mahogany, intercropped with coffee, in both densities, 82 and 41 plants ha-1, after 5 years of implementation of the agroforestry system. Coffee cultivation in agroforestry system with Australian cedar, teak and African mahogany increases the organic matter and P content of the soil, but acidifies the soil and does not influence its physical attributes. The agroforestry system with teak and African mahogany increases coffee yield. Key words: Coffea arabica; Intercropping; Shading; Soil fertility.